Digitizing the public administration and safeguarding individual rights: automated decision-making at the intersection of the GDPR and Polish administrative procedure - Geburczyk, Filip (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2021)
Automating administrative decision-making through the use of algorithms integrated into administrative procedures constitutes a major goal of both the Polish government and the EU. Notwithstanding the undeniable benefits of automated administrative decision-making, the tentative development of the law regulating administrative procedures in this regard translates into risks to important elements of administrative due process. Although a systematic regulatory approach to automated administrative decision-making is lacking, an analysis of the provisions of the GDPR concerning profiling algorithms and automated decision-making may prove rewarding, given that they may directly affect the procedural rights of parties in proceedings before national authorities. On the other hand, the imprecise language of the GDPR makes it susceptible to interpretations deeply embedded in the hitherto elaborated practices of the Polish administrative procedure. The article analyses the intersection between the GDPR and Polish administrative procedure in order to examine the potential for mutual influences between both frameworks.